2010
DOI: 10.1039/b918472d
|View full text |Cite
|
Sign up to set email alerts
|

Ink-jet printed p-type polymer electronics based on liquid-crystalline polymer semiconductors

Abstract: Poly (2,5-bis(3-alkylthiophen-2-yl)thieno [3,2-b]thiophenes) (pBTTTs)-currently one of the most promising class of polymer semiconductors-are known to have a low-room-temperature solubility in a broad range of common organic solvents. By judicious selection of a suitable solvent for these rigidrod-like, liquid-crystalline materials, we ink-jet printed poly(2,5-bis(3-dodecylthiophen-2-yl)thieno[3,2b]thiophene) (pBTTT-C 12 ) into discrete thin-film field-effect transistors (FETs) that display on/off ratios of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…Higher mobilities (up to 0.1 cm 2 V −1 s −1 ) were reached by Baklar et al with another polythiophene derivative, namely, the poly(2,5‐bis(3‐alkylthiophen‐2‐yl)‐thieno[3,2‐b]thiophene) (pBTTT) dissolved in 1,2,4‐trichlorobenzene.…”
Section: Functional Inks For Inkjet‐printingmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher mobilities (up to 0.1 cm 2 V −1 s −1 ) were reached by Baklar et al with another polythiophene derivative, namely, the poly(2,5‐bis(3‐alkylthiophen‐2‐yl)‐thieno[3,2‐b]thiophene) (pBTTT) dissolved in 1,2,4‐trichlorobenzene.…”
Section: Functional Inks For Inkjet‐printingmentioning
confidence: 97%
“…Inkjet‐printing of TIPS‐pentacene at room temperature is also reported . Thiophene‐based semiconductors are normally printed at room temperature or on slightly heated substrates (temperatures up to 50 °C) . On such semiconductors, no postdeposition treatments are usually reported, even if in a few cases annealing at 120 °C in inert atmosphere was done to remove residual solvents and relax the polymer chains in the film.…”
Section: Functional Inks For Inkjet‐printingmentioning
confidence: 99%
“…The pBTTT polymer is known for its excellent charge mobility in eld effect transistor devices. [31][32][33] Even if they yield moderate efficiency in solar cells, pBTTT:fullerene blends are particularly suitable model systems to study microstructural effects. 22 Indeed, it has been shown that the fullerene molecules intercalate between the side-chains of ordered polymer domains, forming a well-dened co-crystalline phase, while excess fullerenes aggregate into relatively phase-pure clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, organic devices are lightweight, which is especially suitable for mobile applications. In addition, evaporation [10], spin coating [11], solution processing [12], and inkjet printing technology [13]- [16] are feasible to realize organic electronic devices. OTFT is a key member in the family of organic electronic devices, and it could be applied to large-area flat-panel displays [17], radio frequency identification card (RF-ID) [18], [19], electronic paper, electronic textile [20], sensors [21]- [24], and so on.…”
Section: Improved Performance Of Pentacene Otftsmentioning
confidence: 99%